Continuous heart rate dynamics preceding in-hospital pulseless electrical activity or asystolic cardiac arrest of respiratory etiology. (October 2022) - Shan, Rongzi; Yang, Jason; Kuo, Alan; Lee, Randall; Hu, Xiao; Boyle, Noel G.; Do, Duc H.
Abstract: Introduction: Respiratory failure is a common cause of pulseless electrical activity (PEA) and asystolic cardiac arrest, but the changes in heart rate (HR) pre-arrest are not well described. We describe HR dynamics prior to in-hospital cardiac arrest (IHCA) among PEA/asystole arrest patients with respiratory etiology. Methods: In this retrospective study, we evaluated 139 patients with 3–24 hours of continuous electrocardiogram data recorded preceding PEA/asystole IHCA from 2010-2017. We identified respiratory failure cases by chart review and evaluated electrocardiogram data to identify patterns of HR changes, sinus bradycardia or sinus arrest, escape rhythms, and development right ventricular strain prior to IHCA. Results: A higher proportion of respiratory cases (58/73, 79 %) fit a model of HR response characterized by tachycardia followed by rapid HR decrease prior to arrest, compared to non-respiratory cases (30/66, 45 %, p  < 0.001). Among the 58 respiratory cases fitting this model, 36 (62 %) had abrupt increase in HR occurring 64 (IQR 23–191) minutes prior to arrest, while 22 (38 %) had stable tachycardia until time of HR decrease. Mean peak HR was 123 ± 21 bpm. HR decrease occurred 3.0 (IQR 2.0–7.0) minutes prior to arrest. Sinus arrest occurred during the bradycardic phase in 42/58 of cases; escape rhythms were present in all but 2/42 (5 %) cases. Right ventricular strain ECG pattern, when present, occurred at a median of 2.2 (IQR −0.05–17) minutes prior to onset of HR decrease. Conclusion: IHCAs of respiratory etiology follow a model of HR increase from physiologic compensation to hypoxia, followed by rapid HR decrease prior to arrest.